Child Labour and its effect on School Education: A Legal Study - Naqvi, Ali; Dixit, Apoorva (Journal of Neonatal Surgery, 2025)
Objective: To assess the effect of child labour on the school education and the school dropout ratio. To find the root cause relating to the school children working as child labourers. To prove that schooling and child labour cannot be done together. Research questions: What is the effect of child labour on the school life of a child? What are the root causes, due to which a school student works as a child labourer? Research type: Doctrinal.